Sustainable strategies on cultivation, modification and rehydration of bacterial cellulose to overcome hornification for industrial applications: A review - Muyao Du; Zhenlei Xiao; Yangchao Luo (Carbohydrate Polymer Technologies and Applications)
Bacterial cellulose (BC) is a polysaccharide biosynthesized by specific microorganisms. Different cultivation methods enable the production of BC in various morphologies. Due to its exceptional physicochemical and colloidal properties, BC has found widespread applications in the biomedical and food industries, but its high production costs remain a challenge to commercialization. In recent years, efforts have focused on utilizing agricultural and food industry by-products as alternative culture media to enhance cost-effectiveness. However, hornification of cellulose during drying causes BC to lose most of its properties, presenting challenges for storage and transportation. By extrusion through cellulose synthase on the bacterial surface, BC is naturally formed as a highly porous 3D structure with abundant hydroxyl groups, allowing for various modifications to improve rehydration. This review provides a comprehensive overview of BC biosynthesis, examining the influence of bacterial strains, culture media, and cultivation methods on its structure and yield. Furthermore, it explores the challenges posed by hornification and highlights recent advances in modification strategies, both in situ and ex situ, to improve the rehydration performance of BC. The modification strategies summarized in this review can serve as a basis for the process design of rehydratable BC that promotes broader commercialization in food, agriculture and biomedical industries.